DNA-based small molecules for hole charge injection and channel passivation in organic heptazole field effect transistors. (13th January 2017) - Cho, Youngsuk; Lee, Junyeong; Lim, June Yeong; Yu, Sanghyuck; Yi, Yeonjin; Im, Seongil
Abstract: DNA-based small molecules of guanine, cytosine, thymine and adenine are adopted for the charge injection layer between the Au electrodes and organic semiconductor, heptazole (C26 H16 N2 ). The heptazole-channel organic field effect transistors (OFETs) with a DNA-based small molecule charge injection layer showed higher hole mobility (maximum 0.12 cm 2 V −1 s −1 ) than that of a pristine device (0.09 cm 2 V −1 s −1 ). We characterized the contact resistance of each device by a transfer length method (TLM) and found that the guanine layer among all DNA-based materials performs best as a hole injection layer leading to the lowest contact resistance. Since the guanine layer is also known to be a proper channel passivation layer coupled with a thin conformal Al2 O3 layer protecting the channel from bias stress and ambient molecules, we could realize ultra-stable OFETs utilizing guanine/Au contact and guanine/Al2 O3 bilayer on the organic channel.